Oral health practice and health-related quality of life of a group of children during the early stage of the COVID-19 pandemic in Istanbul - Işıl Özgül Kalyoncu; Gizem Özcan; Betül Kargül (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: During the pandemic period of coronavirus disease, appropriate oral health management and disease prevention of children are very important for children's oral and general health. The aim of this study was to survey to better understand in children's dental health and dietary habits and to learn about parents' attitudes toward dental treatment and clinical factors associated with their QoL using the Turkish version of KIDSCREEN-10 during the initial stage of the COVID-19 pandemic in the general public. MATERIALS AND METHODS: A two-part questionnaire , namely Part 1 addressed topics regarding changes in general and dental health, dietary habits of children under quarantine, and sociodemographic characteristics of the family and Part 2 impact of QoL was assessed by the KIDSCREEN-10 scale with 10 questions. The questionnaire was sent online using WhatsApp to a convenience sample of mothers with children between the age group of 8 and 18 years, who lived in Istanbul. Variables were statistically analyzed using the Student's t-test for independent samples and Univariate F-test, ANOVA according to the characteristics of variables which were analyzed. RESULTS: This study included 328 from 557 mothers with 58% respondent rate. The consumption of fast food, packaged food, and carbonated beverages decreased during the COVID-19 outbreak. Half of the mothers of children reported that they were anxious or fearful about their children visiting dentists during the pandemic and 64.2% of the children missed routine dental visits. The KIDSCREEN-10 scores for 13 years old or older children were influenced more by the COVID-19 pandemic than those for the 8-12 years old, who had a better QoL (P = 0.008). CONCLUSIONS: The results of this study emphasize the importance of oral health and QoL of children during the initial phase of the COVID-19 outbreak. The general perception of QoL in this group of Turkish children seemed to be substantially affected by COVID-19 outbreak.